Perforated jejunal diverticula in a young woman: A case report - Hardon, Sem F. (Int J Surg Case Rep, 2021)
INTRODUCTION AND IMPORTANCE: Small bowel diverticulosis is a rare condition. It usually remains asymptomatic and undiscovered, until potentially severe complications such as diverticulitis or even perforation occur. We present an unusual case and discuss the pathophysiology, diagnostics strategies, and possible surgical intervention. CASE PRESENTATION: A young woman was referred to our emergency department suffering from acute abdominal pain. A computed tomography scan showed signs of small bowel perforation of unknown origin. Exploratory laparotomy revealed multiple perforated jejunal diverticula (JD). The patient underwent segmental resection of the affected jejunum followed by primary anastomosis. Pathological examination confirmed the diagnosis of perforated JD. CONCLUSIONS: Due to its rarity and variable clinical presentation, it can sometimes be challenging to diagnose this potentially life-threatening condition. If the bowel is suspected from perforation; segmental resection is the treatment of choice, preferably followed by direct restoration of the bowel continuity.